African Sustainable Development Report 2022 - United Nations Economic Commission for Africa (United Nations)
The Africa Sustainable Development Report (ASDR) for the year 2022 comes at the midway of the implementation of the 2030 Agenda for Sustainable Development to which world leaders, including African leaders, made commitments in 2015, to end extreme poverty, inequality and climate change by 2030. In addition, the ten-year implementation plan of the African Union’s Agenda 2063, titled, “the Africa We Want,” that was initiated in 2013, ends in 2023. This report is also paramount because it covers the period when the Covid-19 pandemic and the Ukraine-Russia crisis emerged with significant bearing on the implementation of both agendas. The report is aligned with the 2022 High-level Political Forum (HLPF), which reviewed SDGs 4, 5, 14, 15 and 17, focussed on the theme of “Building back better from the Coronavirus disease while advancing the full implementation of the 2030 Agenda for Sustainable Development.” It examines the impact of the Covid-19 pandemic and the Ukraine-Russia crisis in the implementation of the SDGs and related goals of Agenda 2063. It tracks the performance of all African countries using latest data and highlights critical areas that require urgent policy interventions. The report also provides a benchmark with which to assess the scale of the impacts of both shocks on the SDGs. The key findings, and messages, specific policy recommendations as well as the associated data issues that have been relied on are summarized below.